Site-selective iron-catalyzed C-H alkylation of pyrazinones, azauracils and quinoxalinones - Pansare, Vaibhav Ramchandra; Sreelakshmi, N.; Barsu, Nagaraju (Organic Chemistry Frontiers, 2026)
Described herein is an unprecedented iron-catalyzed C(sp2)-H alkylation of pyrazinone, azauracil, and quinoxalinone analogues using ethers and benzyl derivatives, offering broad scope and high functional group tolerance. The method is scalable and enables downstream functionalization. The mechanistic investigations, such as radical trapping, support a radical-mediated pathway.